Fostering Early Childhood Literacy: The Crucial Role of Family Environments - Kurniawati, Febriana; Motimona, Putri Diah; Maryatun, Ika Budi (Universitas Pendidikan Ganesha, 2024)
Early childhood literacy issues are often overlooked, especially in the context of parents' lack of involvement in building a holistic literacy culture in the family environment. Many parents focus too much on early reading, writing and counting (calistung) skills, neglecting the importance of play and language interactions that support children's motor, social and emotional development. In addition, the use of gadgets as a way to soothe children has led to a reduction in active and interactive play activities. This research uses a literature study approach with a systematic literature review method to analyze the importance of literacy culture in the family. Data were collected through scientific journals using certain keywords and then analyzed descriptively. The research subjects were relevant literature on literacy culture development, early childhood and family environment. The results show that strategies that families can implement include: introducing books early on, reading with children, encouraging children to hold books, reducing the use of electronic devices, creating an interactive learning environment, and involving children in daily activities such as playing in the garden, cooking, cleaning the house and other creative activities. In conclusion, family involvement in building a literacy culture can improve children's literacy skills and interest in reading from an early age, with the implication that family education is very important in supporting children's overall literacy development.